ANALYSIS OF EMPLOYMENT STATUS OF COUPLE OF REPRODUCTIVE AGE ON THE INTENTIONS TO USE CONTRACEPTION IN UNMET NEED CONDITIONS - Annisa Intan Kholifatullah; Ana Fitrotul Laili; Miranda Feyza Nur Imania; Elok Dwi Sulistiani; Lutfi Agus Salim (Universitas Airlangga, 2024)
Based on the results of the 2021 Family Data Collection, it was revealed that Ngadiluwih District, Kediri Regency, East Java Province has a high unmet need case of 19.25%. This unmet need case is far below the target set by the RPJMN for 2019-2024. The village with the highest unmet need rate in Ngadiluwih District is Mangunrejo Village with a case of 16.89%. Various factors contribute to the unmet need rate, including socioeconomic conditions. The purpose of this study was to analyze the occupational status of the intention to use contraception in couples of childbearing age with unmet needs in Mangunrejo Village. The research was conducted with a cross-sectional approach through analytic observational methods in Mangunrejo Village in April-June 2022. The method used was interviewing and distributing questionnaires to respondents. The sample used couples of childbearing age who fit the inclusion criteria in Mangunrejo Village. As for the total of 12 respondents working and 12 respondents not working, as many as 61.3% of respondents not working have the intention to use contraception and as many as 47.8% of working respondents have the intention to use contraception. The results of the analysis showed that there was no significant relationship between the employment status of unmet need women with intention to use contraception (p=0.325). So it can be concluded that reproductive couples in Ngadiluwih District who are in unmet need condition, do not intend to use contraception who are all of those who are workers